Charm Purple Coloring Process for Brass Zipper - LIU Yan, TANG Chun-bao, LI Yong, WANG Yong-sen (Cailiao Baohu, 2021)
Charming purple brass zipper has bright color and good decorative effect. At present, there is no report about this technology at home and abroad. In order to fill the technical gap, the charm purple coloring process for brass zipper was investigated, the effects of the various factors on the film color were discussed and the optimal conditions were obtained. Results indicated that the solution for charm purple coloring process of brass zipper had an optimal composition of CuSO4·5H2O 3～5 g/L, SeO2 0.7～0.8 g/L, (NH4)2S2O8 1.5～2.0 g/L, NaCl 1.5～1.7 mg/L, H2SO4 2.0～2.5 mL/L, temperature 30～35 ℃ and time 25～30 s. The thickness of the coloring film was about 400 nm. The process was completed by one-step route with simple operation, stable performance and low cost. Besides, the test results showed that the charm purple film obtained by this process had uniform color, and its wear resistance, enzyme washing resistance and corrosion resistance all met the production requirements.